Numerical Studies of Graphene Hybrid Nanofluids in Flat Plate Solar Collector - Mahamude, Abu Shadate Faisal; Wan Sharuzi, Wan Harun; Kumaran, Kadirgama; Farhana, Kaniz; Devarajan, Ramasamy (IEEE, 2021)
This study aims to present the fundamental properties related to heat transfer of nanofluids and hybrid nanofluids in solar collector numerically. To deduct the energy consumption and to improve the efficiency of the flat plate solar collector, a research study was conducted to expand its wings in various pathways. Computational simulation is one of them and plays a vital role to diminish the cost before the practical experiment. In this study, graphene, CNC nanofluids, and hybrid nanofluids (CNC + graphene) were used for numerical simulations, which were transferred to the header and riser tubes of the collector. Different attributes such as internal energy, heat transfer rate, surface heat transfer coefficient, surface Nusselt number, molecular Prandtl number and skin friction coefficient of nanofluids and hybrid nanofluids were evaluated and compared with the base fluid. The geometry was prepared based on the actual model of the solar collector using a software. The numerical study reported a satisfactory enhancement of internal energy, heat transfer rate, surface heat transfer coefficient of graphene and the hybrid of graphene nanofluids. Besides, nanofluids and hybrid nanofluids performed in a stable non-dimensional number but showed a rising trend in the skin friction coefficient.